Cytokine concentration across the stratum corneum in atopic dermatitis and healthy controls - Maja-Lisa Clausen (Nature Portfolio, 2020)
Abstract Tape stripping is a promising technique for assessment of epidermal biomarkers in inflammatory skin diseases. However, to facilitate its implementation in the clinical practice, a thorough validation regarding sampling strategy is needed. Knowledge of biomarkers variation in concentration across stratum corneum is scarce. Therefore, this study aimed to assess the variability of cytokines across stratum corneum using tape stripping technique by consecutive application of 21 adhesive tapes (D-squame) to lesional and non-lesional skin from 15 patients with atopic dermatitis (AD) and 16 healthy controls. Concentration of cytokines (IL-1α, IL-1b, IL-5, IL-18, IFN-γ, CCL17, CCL22, CCL27, CXCL8, CXCL10, TNF-α, TSLP, VEGFA) was determined in five different depths, using multiplex immunoassay. Comparing tape 4 with tape 21, no cytokine changed significantly in concentration in AD lesional skin. In AD non-lesional skin a small decrease was found for CCL17, CXCL8 and CXCL10. For healthy controls, a decrease was found for IL-1a, IL-1b, VEGFA and an increase for IL-18. Differences were found between AD skin and healthy control skin. Concentration of cytokines was stable across stratum corneum, indicating that sampling of only one tape from the stratum corneum is reliable in reflecting the overall cytokine milieu. Differences between AD and healthy skin confirm robustness of tape stripping for measuring cytokine levels.